2022
DOI: 10.1038/s41598-022-08341-7
|View full text |Cite
|
Sign up to set email alerts
|

Global gene expression responses of Atlantic salmon skin to Moritella viscosa

Abstract: Moritella viscosa is a Gram-negative pathogen that causes large, chronic ulcers, known as winter-ulcer disease, in the skin of several fish species including Atlantic salmon. We used a bath challenge approach to profile the transcriptome responses of M. viscosa-infected Atlantic salmon skin at the lesion (Mv-At) and away from the lesion (Mv-Aw) sites. M. viscosa infection was confirmed through RNA-based qPCR assays. RNA-Seq identified 5212 and 2911 transcripts differentially expressed in the Mv-At compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…In summary, the reproduced detection of M. viscosa -responding genes in this transcriptome study firmly establishes these genes, and those gene pathways where they were enriched, as important in response to winter-ulcer. The fact that the microarray analysis agreed very well with prior studies [ 35 , 36 , 37 ] also provide confidence that the investigation of miRNAs in same materials has the capacity to identify disease relevant miRNAs.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In summary, the reproduced detection of M. viscosa -responding genes in this transcriptome study firmly establishes these genes, and those gene pathways where they were enriched, as important in response to winter-ulcer. The fact that the microarray analysis agreed very well with prior studies [ 35 , 36 , 37 ] also provide confidence that the investigation of miRNAs in same materials has the capacity to identify disease relevant miRNAs.…”
Section: Discussionsupporting
confidence: 78%
“…A study of expression changes in M. viscosa lesion materials applying RNA sequencing was recently reported [ 37 ]. There are several differences between the current study and this RNA seq study (e.g., sampling time points, LS sites sampled, application of two completely different platforms (RNA seq and microarray)) which could lead to different results due to study design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this hypothesis is quite speculative. Eslamloo et al [ 73 ] showed that hsp70 , hsp90aa1 , and cirbp transcript expressions were upregulated, while that of serpinh1 and ucp2 was downregulated, in the skin of ~200 g (8°C acclimated) diploid Atlantic salmon exposed to Moritella viscosa , whereas liver hsp70 , hsp90aa1 and ucp2 transcriptions were upregulated in ~500 g male diploid Atlantic salmon reared at 12 or 20°C and injected with a commercial multivalent vaccine (i.e., Forte Micro; containing formalin-inactivated cultures of several bacterial pathogens) (Ignatz et al, in prep.).…”
Section: Discussionmentioning
confidence: 99%